Examine the parenting style effect on the academic achievement orientation of secondary school students: The moderating role of digital literacy - Hassan, Mehdi; Malik, Asma Seemi; Sang, Guoyuan; Rizwan, Muhammad; Mushtaque, Iqra; Naveed, Shaheryar (Frontiers in Psychology, 2022)
The purpose of the study was to determine the association between parenting styles (authoritative and permissive) and students' self-efficacy (LSE), self-regulatory learning (SRL), and academic accomplishment orientation of secondary school students in Punjab, Pakistan. The study also investigated the effect of digital learning as a moderating variable in the relationship between self-regulatory learning (SRL) and academic achievement oriented, as well as between learner self-efficacy (LSE) and academic achievement among secondary school students. The study was conducted with (N = 720) secondary school students from Punjab, Pakistan. In the current research, cross-sectional design was used, and multistage sampling was used to draw a sample from the population. The results from the study show that the authoritative parenting style has a weak association with learner self-efficacy and a strong association with self-regulatory learning. Permissive parenting styles have low associations with self-regulatory learning and have a high association with learner self-efficacy as compared to authoritarian parenting. Furthermore, when compared to students from permissive parenting, secondary students from authoritarian parenting have higher self-regulatory learning and a higher academic achievement orientation. Results revealed that that digital literacy significantly moderates learners' self-efficacy to influence the academic achievement orientation, while digital literacy significantly interacts with self-regulatory learning to highly influence the academic achievement orientation of secondary school students.